Relationship Elements In Job Satisfaction Of Special Education Teachers In Malaysia - et. al., Parimala A/P Palanisamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Relationship factors with administrators, parents and peers can help teachers to achieve job satisfaction, especially special education teachers. Previous studies have explained that relationships between teachers are very important so that they can work happily, comfortably and contentedly. In doing a job in an organization, the relationship between teachers and headmasters as well as between teachers and teachers must be maintained. Previous studies have also described the relationship between teachers and between teachers and administrators as a catalyst to teacher job satisfaction in schools. This relationship element is also agreed upon as an important element in providing the influence of head teacher leadership on teacher job satisfaction. Relationships in school organization as one of the factors that contribute to the achievement of job satisfaction among teachers. This qualitative study was conducted to examine the views of respondents related to the elements of relationships in determining job satisfaction of special education teachers. Interview sessions were conducted with 11 coordinators of special education integration programs (PPKI) in the state of Johor, Malaysia. The findings of this study are expected to be able to provide a clear picture related to the relationship elements for job satisfaction of special education teachers.